A highly selective and fast-response photoluminescence humidity sensor based on F− decorated NH2-MIL-53(Al) nanorods. Issue 36 (7th September 2017) - Lu, Ting; Song, Hongjie; Dong, Xiaoqun; Hu, Jianyu; Lv, Yi
Abstract : NH2 -MIL-53(Al) nanorods studded with F − were successfully synthesized via coordination modulation with HF as a modulator. Abstract : NH2 -MIL-53(Al) nanorods studded with F − were successfully synthesized via coordination modulation with HF as a modulator. The investigation of the growth mechanism pointed out that F − plays a key role in the formation process. The incorporation of F − into the framework of NH2 -MIL-53(Al) not only made the crystal morphology tunable but also magnified the fluorescence enhancement performance of NH2 -MIL-53(Al) in water vapor, based on which a highly efficient humidity sensor was fabricated. Among different kinds of humidity sensors, the present sensing system stood out due to its fast response rate, good sensitivity and high selectivity with a low detection limit of 0.6 μg mL −1 (S/N = 3) and a wide detection range from 4 to 40 μg mL −1 . On the other hand, a majority of the conventional electronic humidity sensors seriously suffered from temperature dependence, while the present sensing system got over this disadvantage. Therefore, the NH2 -MIL-53(Al) nanorod layer-based fluorescence sensing system has the potential for application in the real-time monitoring of humidity under ambient conditions.